Relationship between relocation of phototropin to the chloroplast periphery and the initiation of chloroplast movement in Marchantia polymorpha. (27th August 2019) - Sakata, Momoko; Kimura, Shun; Fujii, Yuta; Sakai, Takamasa; Kodama, Yutaka
Abstract: The blue‐light photoreceptor kinase phototropin (phot) mediates chloroplast movement in response to light and temperature. Phot predominantly localizes at the plasma membrane, but also resides in the cytosol and the chloroplast periphery. Although the phot localized to the chloroplast periphery is thought to mediate chloroplast movement, the localization mechanism is unknown. In this study, we found that chloroplast movement does not occur in 0‐day‐old gemma cells of the liverwort Marchantia polymorpha but that the movement is induced in 1‐day‐old gemmaling cells. Along with this physiological change, the subcellular localization of phot also changed: In 0‐day‐old gemma cells, phot localized at the plasma membrane and the cytosol, but in 1‐day‐old gemmaling cells, the phot disappeared from the cytosol and appeared at the chloroplast periphery. When the relocalization was tracked using a photoconvertible fluorescent protein, the cytosolic phot relocated to the plasma membrane, and the plasma membrane‐resident phot relocated to the chloroplast periphery. The blue‐light‐dependent activation of phot kinase activity enhanced this relocalization. Mutated phot deficient in blue‐light reception or kinase activity had a severely reduced ability to localize at the chloroplast periphery. These findings suggest that photoactivated phot localizes at the chloroplast periphery to initiate chloroplast movement.